The Role of Cultural Education and Training at the DKI Jakarta Pavilion Taman Mini Indonesia Indah in Maintaining Local Wisdom - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Insani, Alisya Nur; Madyaningrum, Ika Ristiyani (CV ODIS, 2023)
This final report is entitled